Penerapan Pendekatan Modified Free Inquiry Sebagai Upaya Meningkatkan Kreativitas Mahasiswa Calon Guru Dalam Mengembangkan Jenis Eksperimen Dan Pemahaman Terhadap Materi Fisika - Khanafiyah, Siti; Rusilowati, Ani (BERKALA FISIKA, 2010)
This study aimed to enhance students' creativity in developing the kinds of experiments and understanding of materials physics, especially wave, with application of the modified approach to free inquiry in the department of Physics, State UNNES. The instrument used a questionnaire to measure creativity, observation sheet to measure the ability psikhomotorik and sheets test to measure the understanding of matter waves. Results were analyzed using a Likert scale questionnaire. Normalized gain formula is used to test the effectiveness of modified free inquiry approach in enhancing students' creativity and understanding of the matter wave. The results showed that the application of modified free inquiry approach that gives freedom to the students to develop creativity, to (1) improve the ability psikhomotorik students, (2) type of experiment, developed into more varied, (3) enhance student creativity, and (4) increase cognitive abilities of students. Keywords: modified free inquiry, creativity